2019
DOI: 10.3390/mi10060353
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Adaptive Fuel Supply Mechanism in Micro DMFC Based on the Microvalve

Abstract: To achieve a self-adaptive fuel supply mechanism for the micro direct methanol fuel cell (μDMFC), we designed and developed a thermal control microvalve channel structure, where we considered the relationship between the temperature characteristics, viscosity, and velocity of the methanol solution. Both the single channel model and three-dimensional cell model for the microvalve were established using the COMSOL Multiphysics program. The results demonstrated that in the microvalve channel, the viscosity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Accordingly, when the flow path is a hydrophilic surface, the CO 2 bubbles move more easily in the channels and are more easily discharged from the flow field. Thus, on the basis of the relationship linking the viscosity, velocity, and methanol solution temperature at different current densities, the research group also reported the development of a thermal control microvalve channel structure [113]. The expectation was that the microvalve structure could achieve a self-adaptive fuel supply and effectively increase the power and stability during the PS-DMFC operation.…”
Section: Acidic Dmfcsmentioning
confidence: 99%
“…Accordingly, when the flow path is a hydrophilic surface, the CO 2 bubbles move more easily in the channels and are more easily discharged from the flow field. Thus, on the basis of the relationship linking the viscosity, velocity, and methanol solution temperature at different current densities, the research group also reported the development of a thermal control microvalve channel structure [113]. The expectation was that the microvalve structure could achieve a self-adaptive fuel supply and effectively increase the power and stability during the PS-DMFC operation.…”
Section: Acidic Dmfcsmentioning
confidence: 99%
“…Studies reported that the MCO mostly relies on the operating temperature [74][75][76] and the method of delivering the fuel [77]. It is given that the rate of fuel/oxidant delivered, and their concentration will substantially impact MCO [78].…”
Section: Methanol Crossovermentioning
confidence: 99%
“…µDMFC is a new type of energy device with the advantages of having a simple structure, easy operation, and emitting low pollution, which is widely used in aerospace, military, and communication fields [1][2][3][4]. The current collector plays an important role by collecting the conduction current and reasonably distributing the gas and water in the µDMFC.…”
Section: Introductionmentioning
confidence: 99%